TAYYOR MAHSULOT TANNARXI. MAHSULOTNI SOTISH TANNARXI (SOTILGAN MAHSULOT TANNARXI) - Xudaynazarova Dilnoza; Jalilov Shohjahon (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the economic essence of the cost of finished goods and the cost of goods sold (COGS), as well as their formation process and impact on the financial performance of enterprises. The study analyzes the structure of production costs, methods of cost accounting, and modern approaches to determining product cost. In addition, the direct influence of the cost of goods sold on revenue and profit indicators is substantiated. The paper highlights the differences and interrelations between the cost of finished goods and the cost of goods sold, emphasizing their importance in evaluating enterprise efficiency. Based on practical examples, opportunities for cost reduction and cost optimization are explored. The findings of the research contribute to improving cost management practices, enhancing competitiveness, and ensuring financial stability in enterprises.